Effectiveness of Feer Education Program in Improving Knowledge , Attitude, and Risk Behaviour Practices related to HIV Amongst Students at Universiti Putra Malaysia - Ibrahim, Normala (2012)
The objectives of the study were to develop a peer-led education program module on HIV prevention, implement it and examine its effectiveness on university students. A randomized controlled study design was used in this study. A total of 276 respondents were randomly allocated into an intervention or control group. The intervention group received a five hour peer-led education program on HIV information and life skills on HIV prevention while the control group was given sessions on stress management and effective communication skills of similar duration. A validated, pretested questionnaire was used to measure the outcome on knowledge, attitude and risk behaviour practices related to HIV at baseline, immediate post test and three months follow up. The results showed there was a significant improvement in respondents’ HIV knowledge in the intervention group at immediate post test and three months follow up with a small effect size (p = 0.0001, partial η2 = 0.056). The intervention module was also effective in improving attitude related to HIV at immediate post test with a large effect size (p = 0.0001, partial η2 = 0.202). The improvement in substance risk behaviour was significant at three months follow up with a small effect size (p = 0.006, partial η2 = 0.027). However, there was no significant improvement in sexual risk behaviour observed after intervention (p = 0.993, partial η2 = 0.004). The interaction between group, time and ethnicity was significant for attitude related to HIV (p = 0.017) and substance risk behaviour (p = 0.0001). There was also significant interaction between group, time and gender for sexual risk behaviour (p = 0.039).